Cost-effectiveness analysis of nivolumab plus ipilimumab versus platinum-doublet chemotherapy for first-line treatment of stage IV or recurrent non-small cell lung cancer in the United States. (31st December 2022) - Berling, Malin; Chaudhary, Mohammad A.; Yuan, Yong; Varol, Nebibe; Dale, Peter; Testa, Eleonora; Klint, Johan; Lee, Adam; Lubinga, Solomon J.; Penrod, John R.
Abstract: Aim: We evaluated the cost-effectiveness of nivolumab in combination with ipilimumab (NIVO + IPI) versus platinum-doublet chemotherapy (PDC) for the first-line treatment of stage IV or recurrent non-small cell lung cancer (NSCLC) from a third-party payer perspective in the United States (US). Methods: A partitioned survival model was developed using efficacy, safety, and utility inputs derived from Part 1 of the phase 3 CheckMate 227 trial (NCT02477826) with 37.7-month minimum follow-up for overall survival (OS). OS and progression-free (PF) survival were extrapolated over a 20-year time-horizon using parametric spline-based models selected based on goodness of fit and validated with data from external sources. Duration of treatment Kaplan–Meier curves were used for treatment cost calculations. US-specific costs (2021 dollars) for drug acquisition, administration, and monitoring; disease management (PF and progressed disease health states); end-of-life care; adverse events; and subsequent treatments were derived from publicly available sources. Time-to-death utilities were applied in the base case, whereas treatment-specific progression-based utilities were tested in a scenario analysis. Main outcomes included incremental cost per life-year gained (LYG) and quality-adjusted life-year (QALY). Model uncertainty was assessed through deterministic and probabilistic sensitivity analyses. Results: NIVO + IPI resulted in 1.53 additional life-years, 1.33 additional QALYs, and 142 088 in additional costs compared with PDC. The incremental cost per LYG was 92 651, whereas incremental cost per QALY gained was 106 553. The application of treatment-specific progression-based utilities yielded an incremental cost per QALY gained of 117 076. Probabilistic sensitivity analysis revealed a 98% probability that NIVO + IPI was cost-effective versus PDC at a willingness-to-pay threshold of 150 000 per QALY. Conclusions: NIVO + IPI was estimated to be cost-effective as a first-line treatment for stage IV or recurrent NSCLC in the US, with increased survival and higher cost compared with PDC.